2020
DOI: 10.12911/22998993/125586
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Manipulation of Psidium guajava to Facilitate Secondary Forest Succession in Tropical Forests

Abstract: Psidium guajava L. has been documented as an exotic invasive species in many parts of the world, but little is known about its interactions with native woody species during secondary forest succession in tropical forests. Its invasion and interactions with native species in different stages of secondary forest succession were assessed in Kakamega Rainforest in western Kenya. The study covered three forest blocks each with five different forest types, namely: open fields, young secondary forest, middle-aged sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The species exhibits pioneer characteristics and canonizes new sites devoid of any tree growth, mainly steep hill slopes occupied by grasses. In Kenya, the study conducted by Otuoma [38] shows that guava has displaced native plant species; however, he also concluded that the presence guava as overhead shade trees in ecological restoration areas has supported the growth of shade-tolerant native tree species.…”
Section: Discussionmentioning
confidence: 99%
“…The species exhibits pioneer characteristics and canonizes new sites devoid of any tree growth, mainly steep hill slopes occupied by grasses. In Kenya, the study conducted by Otuoma [38] shows that guava has displaced native plant species; however, he also concluded that the presence guava as overhead shade trees in ecological restoration areas has supported the growth of shade-tolerant native tree species.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, seedling production in guava plants is an important phase that influences the success and final production of the crop [33], as well as the restoration of degraded areas. Disturbances that occur naturally or from climatic changes can cause higher light intensity, promoting the initial establishment of P. guajava in degraded areas by creating a shaded environment beneficial to the growth of shadow-tolerant native species [34].…”
Section: Introductionmentioning
confidence: 99%